Coaching in Organizations (A Study on the Implementation of Coaching in Indonesian Banking) - Pramana, Iwan; Sammy Kristamuljana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to see how far the implementation of coaching in major banks in Indonesia. These banks were chosen because of their great influence on the Indonesian economy. This study is interesting because according to its purpose, coaching will be able to trigger individual performance that will have an impact on organizational performance. Although until now there has been no single agreement on the definition of coaching, the coaching methods used in these banks are similar. This study uses a qualitative approach by conducting interviews through purposive sampling. Informants are people who play a very important role in planning, implementing and evaluating the coaching that is carried out. Thematic analysis was carried out to classify the data obtained. As a result, there are differences among these banks in carrying out the coaching process. The benefit of this study is that we can find out the path that can be used to optimize the coaching process in order to form a coaching culture.